Individual wages and regional market potential1: Evidence from the Polish Labour Force Survey. Issue 4 (7th July 2016) - Cieślik, Andrzej; Rokicki, Bartłomiej
Abstract: In this article, we study wage determinants in Poland by employing the augmented NEG wage equation that controls for individual worker characteristics. Our analysis is based on the Labor Force Survey (LFS) conducted by the Polish Central Statistical Office (CSO) for the period 1999–2009. Using annual data on about 10, 000 Polish workers in 16 regions, we find that a significant fraction of inter‐individual wage differences can be explained by the geography of access to markets.